2020
DOI: 10.21608/scumj.2020.119622
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic and Histopathological Findings in Patients with Various Lower Gastrointestinal Symptoms: A Single-Center Experience

Abstract: Background: Early diagnosis of lower gastrointestinal (GI) diseases constitutes a challenge. While colonoscopy helps in the detection of these diseases; histopathological analysis of obtained biopsies is of greater importance. Aim: This study aimed at the identification of colonic lesions associated with common lower GI manifestations based on colonoscopy and histopathological examination of biopsies. Materials and Methods: In a retrospective cross-sectional study, we included medical records of 710 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 14 publications
3
7
0
Order By: Relevance
“…Consistent with studies by Denis et al, Moussa et al, and Bhagyalakshmi et al, the malignancies were predominantly found in specific histopathology. 13,14,16 Our investigation also discovered that adenomatous polyp was found in 4% of the subjects. Based on colorectal cancer pathogenesis, the adenomatous polyp may develop into colorectal cancer.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Consistent with studies by Denis et al, Moussa et al, and Bhagyalakshmi et al, the malignancies were predominantly found in specific histopathology. 13,14,16 Our investigation also discovered that adenomatous polyp was found in 4% of the subjects. Based on colorectal cancer pathogenesis, the adenomatous polyp may develop into colorectal cancer.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast with a study from Moussa et al, the majority of NSCC histopathology findings admitted due to chronic diarrhea accompanied by hematochezia. 14 Specific results from histopathologic findings in this study mainly were malignancy and inflammatory bowel disease (IBD). Consistent with studies by Denis et al, Moussa et al, and Bhagyalakshmi et al, the malignancies were predominantly found in specific histopathology.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations